INTEGRASI DIGITAL PLATFORM LEARNING BERBASIS GAMIFIKASI DALAM PEMBELAJARAN SOSIOLOGI DI SMAN 1 LUHAK NAN DUO - Meta, Erza; Hefni; Erningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the fact that in the world of education in the digital era, the use of technology and communication is very important to be applied in learning. The utilization of digital platform learning based on gamification is one effective way to support the learning process. Gamification is an approach that combines game elements into a game context. One form of platform used is Minecraft, Quizizz, and Kahoot. This effort is done as a way to increase student motivation and make it easier for teachers in the learning process to be more effective and efficient. Therefore, this study aims to determine the integration of digital platform learning based on gamification in sociology learning. This research uses qualitative research with a descriptive type. The theory used in this research is the constructivism theory by Jean Piaget. The informants in this study are teachers, students, deputies, and principals at SMAN 1 Luhak Nan Duo. The sample of this study consisted of 11 people with certain criteria or sampling with purposive sampling technique. Data collection techniques used are observation, interviews, and document studies. Data analysis uses the Miles and Huberman model, starting from data collection, data reduction, data presentation, and conclusion drawing (verification). The results show that overall, the integration of digital platform learning based on gamification in sociology learning at SMAN 1 Luhak Nan Duo has been running quite well. The Minecraft platform is used during the learning process, and the Quizizz and Kahoot platforms are used as evaluation tools. Efforts are needed to improve the process of implementing digital platform learning based on gamification in sociology learning at SMAN 1 Luhak Nan Duo to make it even better.